2017
DOI: 10.1111/padm.12340
|View full text |Cite
|
Sign up to set email alerts
|

Exploring frontline work in China

Abstract: This study of the state frontline workforce breaks new ground by conducting an institutional analysis of rule abidance in the People's Republic of China (PRC). We draw upon a survey (n = 1,721) of Chengguan officers, the main players in regulatory enforcement of civil law in urban China, to explore the influence of autocratic one‐party rule on the meaning of and variation in rule abidance in China. The majority of Chengguan officers are rule followers, and demographic differences show little deviation from thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…To reverse the traditional weak and selective enforcement of water‐related and environmental laws (Linster and Yang ), rule‐following leaders emphasize the importance of executing legislation consistently. In their study on rule abidance among Chinese frontline officers, Zang and Musheno () found that the majority were rule followers. Rule following ensures predictability and prevents abuses of power and corruption that can seriously hurt the government's legitimacy and threaten one‐party rule (Zhu, Huang, and Zhang ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…To reverse the traditional weak and selective enforcement of water‐related and environmental laws (Linster and Yang ), rule‐following leaders emphasize the importance of executing legislation consistently. In their study on rule abidance among Chinese frontline officers, Zang and Musheno () found that the majority were rule followers. Rule following ensures predictability and prevents abuses of power and corruption that can seriously hurt the government's legitimacy and threaten one‐party rule (Zhu, Huang, and Zhang ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Our ambition was to inductively identify a variety of perverse effects and to establish a theoretical understanding of the nature of these perverse effects and their relation to key features of public innovation. This resulted in the following set of articles and books: Altshuler and Behn (1997), Ansell and Torfing (2014), Borins (2001Borins ( , 2002, Bekkers et al (2006Bekkers et al ( , 2011, Brandsen et al (2016), Brown and Osborne (2013), De Vries et al (2016), Fuglsang and Sundbo (2016), Hartley (2005), Jordan (2014), Moore and Hartley (2008), Osborne and Brown (2005), O'Toole (1997), Roberts and King (1996), Sørensen and Torfing (2011), Voorberg et al (2015), Windrum and Koch (2008), and Zang and Musheno (2017). We analyzed these key sources in the literature on public innovation for information about and examples of perverse effects.…”
Section: Strategy For Mapping the Dark Side Of Public Innovationmentioning
confidence: 99%
“…On the other hand, supervisors bear little risk for rule deviation, because they can use their subordinates as scapegoats if things go wrong. Shifting blame to subordinates is a common survival strategy for government officials in China (Zang and Musheno ). Thus, we propose two hypotheses with respect to organizational red tape and bureaucratic power:
Hypothesis 5 : Bureaucrats who perceive a high level of red tape will exhibit a higher level of corruptibility, all other factors being equal.
Hypothesis 6 : Bureaucrats with greater bureaucratic power will have a higher level of corruptibility, all other factors being equal.
…”
Section: A Comprehensive Frameworkmentioning
confidence: 99%
“…On the other hand, supervisors bear little risk for rule deviation, because they can use their subordinates as scapegoats if things go wrong. Shifting blame to subordinates is a common survival strategy for government officials in China (Zang and Musheno 2017). Thus, we propose two hypotheses with respect to organizational red tape and bureaucratic power:…”
Section: Work-related Opportunitiesmentioning
confidence: 99%